Strategic Analysis of PT Cisarua Mountain Dairy Tbk (CMRY) - Melinda, Putu Bunga Mutiara (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the most appropriate strategy to support the business expansion of PT Cisarua Mountain Dairy Tbk (Cimory), a leading player in Indonesia’s food and beverage industry. Amid global economic uncertainty and slowing domestic growth, companies in this sector must innovate and adapt their strategic approaches. The research adopts a strategic management framework consisting of three stages: input stage (including PEST analysis, Porter’s Five Forces, EFE and IFE matrices, and Competitive Profile Matrix), matching stage (SWOT, SPACE, BCG, IE, and Grand Strategy matrices), and decision stage using the Quantitative Strategic Planning Matrix (QSPM). The analysis identifies market development as the most suitable strategy, emphasizing international market expansion through consumer behavior research, optimized distribution systems, and product innovation aligned with global market preferences.